2022
DOI: 10.31004/edukatif.v4i3.2820
|View full text |Cite
|
Sign up to set email alerts
|

Management of Islamic Education in the Challenges of Society 5.0

Abstract: Today, Islamic education is faced with challenges in welcoming the society 5.0. The challenge is to focus more on improving human resources because the society 5.0 places humans as the main component. Therefore, it is very important in the management of Islamic education to always exist and face the challenges of the society 5.0. This research is a literature study that interprets the data in a descriptive analysis. This study aims to see and examine the problems and challenges and the strategies used by Islam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
3
0
2
Order By: Relevance
“…Resufle and Rofiki concluded that in facing society 5.0 era, Islamic educational institutions must prepare human resources with reliable digital skills, have the ability to think creatively and innovatively [30]. This is in line with the conclusion in [31] confirming that society limits human functions in carrying out every activity.…”
Section: Introductionsupporting
confidence: 66%
“…Resufle and Rofiki concluded that in facing society 5.0 era, Islamic educational institutions must prepare human resources with reliable digital skills, have the ability to think creatively and innovatively [30]. This is in line with the conclusion in [31] confirming that society limits human functions in carrying out every activity.…”
Section: Introductionsupporting
confidence: 66%
“…Copyright (c) 2022 by Istawa. All Right Reserved DOI: 10.24269/ijpi.v7i2.5750 life skills, for dealing with society 5.0 is to prepare human resources with digital skills and innovative and creative thinkers; change the paradigm of educational institutions; and preparing educational institution leaders who have leadership qualities and can collaborate (Resufle & Rofiki 2022). In line with the research by Husni & Nabil (2022) it was revealed that there were several suggestions put forward in dealing with er 5.0. among others: (1) eliminating dualism between science and religion;…”
Section: Discussionmentioning
confidence: 91%
“…(Ahyar et al, 2020). Wu dan Hung mengatakan juga bahwa evaluasi kinerja menjadi bagian dari manajemen dan sistem kontrol yang membantu organisasi dalam mengelola sumber daya dan mengembangkan pekerjaan secara efektif dan efisien (Mora et al, 2016, Reshufle & Rofiki, 2022. Maka pendampingan berperan penting dalam kontribusi tersebut.…”
Section: Diskusiunclassified